LINGKUNGAN KERJA, MOTIVASI INTRINSIK, DAN KEPRIBADIAN PROAKTIF SERTA EFEKNYA TERHADAP KREATIVITAS KARYAWAN - Apriadi, Wiken Pramasinta; Dewi, I Gusti Ayu Manuati (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.12.NO.02.TAHUN.2023DO - 10.24843/EEB.2023.v12.i02.p04, 2023)
This study aims to analyze the effect of work environment, intrinsic motivation and proactive personality on the creativity of employees at CV. Aulia Fajar Collection Group. The theory used in this study is the theory of character activation. The population is all employees in the production section of CV. Aulia Fajar Collection Group. The number of samples used was 60 people using saturated sampling technique, where all members of the population were used as research samples. The data collection method used interviews and questionnaires and the data were analyzed using Multiple Linear Regression. The results of the analysis show that the work environment, intrinsic motivation, and proactive personality have a positive and significant effect on the creativity of employees in the production sector of CV. Aulia Fajar Collection Group Theoretically, the results of this study provide support for the trait activation theory. Practically, the results of this study are expected to be a reference for the management of CV. Aulia Fajar Collection Group in order to increase the creativity of its employees